Calcium Signaling in Aging and Neurodegenerative Diseases 2019 - Cortes, Luísa (2020)
The European Calcium Society (ECS) workshop, which is held every 2 years, is a dedicated meeting of scientists interested in the elucidation of the action of calcium binding, calcium signaling and the study of proteins and organelles, such as mitochondria and endoplasmic reticulum, thereby involved, either in health and disease conditions. The 8th edition of the ECS workshop was organized by a group of researchers from the University of Coimbra, Portugal, in close collaboration with ECS board members. Thanks to the central role of “Calcium Signaling in Aging and Neurodegenerative Disorders”, the ECS 2019 workshop was attended by 62 experts who presented their results in a plenary lecture and five regular symposia, two oral communication sessions and two poster sessions, followed by a hands-on session on calcium imaging. All the scientific and social events were fully participated by the scientific community that allowed a close and fruitful interaction and discussion between junior researchers and senior experts in the field. In this report, the contributions in individual sessions are summarized.